2013
DOI: 10.1111/ajt.12062
|View full text |Cite
|
Sign up to set email alerts
|

Early Plasma Soluble Receptor for Advanced Glycation End-Product Levels Are Associated With Bronchiolitis Obliterans Syndrome

Abstract: Early epithelial injury after lung transplantation may contribute to development of bronchiolitis obliterans syndrome (BOS). We evaluated the relationship between early post-operative soluble receptor for advanced glycation end product (sRAGE) levels, a marker of type I alveolar cell injury, and BOS. We performed a cohort study of 106 lung transplant recipients between 2002 and 2006 at the University of Pennsylvania with follow-up through 2010. Plasma sRAGE was measured 6 and 24 hours after transplantation. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…Soluble RAGE (sRAGE) is detectable in plasma but data are conflicting regarding its correlation with cardiovascular disease (35)(36)(37). Recently, sRAGE levels were correlated with BOS development in patients following LTx (38). This supports the hypothesis that glycation is a mechanism by which DM may cause lung pathology and supports our finding that BOS may be accelerated in the presence of hyperglycemia.…”
Section: Discussionsupporting
confidence: 83%
“…Soluble RAGE (sRAGE) is detectable in plasma but data are conflicting regarding its correlation with cardiovascular disease (35)(36)(37). Recently, sRAGE levels were correlated with BOS development in patients following LTx (38). This supports the hypothesis that glycation is a mechanism by which DM may cause lung pathology and supports our finding that BOS may be accelerated in the presence of hyperglycemia.…”
Section: Discussionsupporting
confidence: 83%
“…Elevated levels represent lung injury and are associated with impaired alveolar fluid clearance and increased risk of pulmonary oedema . Normal values are ≤ 2 pg.ml −1 , and, therefore, all of our values were elevated, with a peak and statistically significant difference at 4 h. A correlation between elevated sRAGE levels and worsening primary graft dysfunction grade has been reported . Our study demonstrated higher levels of sRAGE in the alveolar recruitment group between 1 h and 4 h after first lung reperfusion.…”
Section: Discussionsupporting
confidence: 50%
“…Increased plasma levels of sRAGE were associated with primary graft dysfunction at six and 24 hours after lung transplantation [59]. Elevated plasma sRAGE measured 24 hours postoperatively was associated with the development of bronchiolitis obliterans syndrome [60]. No data exist on RAGE and lung transplantation for iPAH.…”
Section: Discussionmentioning
confidence: 99%